Spiral drawing analysis with a smart ink pen to identify Parkinson's disease fine motor deficits - Toffoli, Simone; Lunardini, Francesca; Parati, Monica; Gallotta, Matteo; De Maria, Beatrice; Longoni, Luca; Dell'Anna, Maria Elisabetta; Ferrante, Simona (Frontiers in Neurology, 2023)
INTRODUCTION: Since the uptake of digitizers, quantitative spiral drawing assessment allowed gaining insight into motor impairments related to Parkinson’s Disease. However, the reduced naturalness of the gesture and the poor user-friendliness of the data acquisition hamper the adoption of such technologies in the clinical practice. To overcome such limitations, we present a novel smart ink pen for spiral drawing assessment, intending to better characterize Parkinson’s Disease motor symptoms. The device, used on paper as a normal pen, is enriched with motion and force sensors. METHODS: 45 indicators were computed from spirals acquired from 29 Parkinsonian patients and 29 age-matched controls. We investigated between-group differences and correlations with clinical scores. We applied machine learning classification models to test the indicators ability to discriminate between groups, with a focus on model interpretability. RESULTS: Compared to control, patients’ drawings were characterized by reduced fluency and lower but more variable applied force, while tremor occurrence was reflected in kinematic spectral peaks selectively concentrated in the 4-7Hz band. The indicators revealed aspects of the disease not captured by simple trace inspection, nor by the clinical scales, which, indeed, correlate moderately. The classification achieved 94.38% accuracy, with indicators related to fluency and power distribution emerging as the most important. CONCLUSION: Indicators were able to significantly identify Parkinson’s Disease motor symptoms. Our findings support the introduction of the smart ink pen as a time-efficient tool to juxtapose the clinical assessment with quantitative information, without changing the way the classical examination is performed.